The New Democratic Party in the Era of Neoliberalism - Evans, Bryan (Rethinking the Politics of Labour in Canada, 2012)
Provides a critical assessment of labour's longstanding relationship with the NDP and makes the case that organized labour's own "culture of defensiveness" has helped to maintain its enduring links with the NDP, despite the party's diminishing interest in projects historically associated with social democracy. –Editor's introduction
Keywords: History; Labor Unions; Labor movement; Political activity; Political aspects